Perceptibility and Acceptability of Surface Gloss Variations in Dentistry - Rocha, R. S. [UNESP]; Fagundes, T. C. [UNESP]; Caneppele, T. M. F. [UNESP]; Bresciani, E. [UNESP] (Operative Dentistry Inc, 2020)
Objective: To assess the visual perception of observers regarding perceptibility and acceptability of surface gloss variations of resin composites and to determine the limit of perceptibility and acceptability of gloss variations. Methods: Eight resin composite specimens and one human tooth specimen were fabricated. The resin specimens were polished to reach a surface gloss, in gloss units (GUs), of 10 GU, 20 GU, 30 GU, 40 GU, 50 GU, 60 GU, 70 GU, and 80 GU, and the human tooth specimen had a surface gloss of 80 GU. Sixty observers were selected to compare the surface gloss of the specimens in a light booth. For the perceptibility assessment, specimens were randomly displayed two at a time. Each observer performed a total of 144 observations. Observers answered two specific questions for determining the level and limit of perceptibility of gloss variations. The acceptability limit of gloss was determined by comparing the resin specimens with the tooth specimen. The observations were performed with dental practice scenarios (illuminant conditions, visualization field, and observers' education). Data were submitted to a nonlinear probit model and nonlinear regression estimation probit (5%). Results: Differences in perceptibility and acceptability were observed for surface gloss variations (AGU) (p<0.001). Perceptibility in- creased with AGU (10<20<30<40<50=60=70), while acceptability decreased with AGU (0=10>20>30>40>50>60=70). Acceptability and perceptibility limits were 6.4 GU and 35.7 GU, respectively. Conclusions: Perceptibility and acceptability of surface gloss are influenced by gloss variations. A variation of 6.4 GU was required for 50% of observers to notice gloss variations. Concerning acceptability, observers required a variation of 35.7 GU to consider differences in gloss not acceptable.